2014
DOI: 10.1002/ps.3817
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach: Beauveria bassiana granules applied to nursery soil for management of rice water weevils in paddy fields

Abstract: Applications of millet-based B. bassiana granules on rice nursery soil can be an effective and efficient biological control strategy for the management of rice water weevils. This method can be relatively inexpensive and requires less labor than practices involving the spraying of fungi directly on rice in paddy fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Moreover, the growth of fungi in the medium supplemented with chitin resulted in conidia with better quality compared to chitinfree medium. Carbon and Nitrogen have the ability to increase the formation of mycelium and germination of conidia (Guerrero et al 2007;Hou et al 2013;Kim et al 2014). The highest production of conidia in B. bassiana in this study was shown in P9 treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, the growth of fungi in the medium supplemented with chitin resulted in conidia with better quality compared to chitinfree medium. Carbon and Nitrogen have the ability to increase the formation of mycelium and germination of conidia (Guerrero et al 2007;Hou et al 2013;Kim et al 2014). The highest production of conidia in B. bassiana in this study was shown in P9 treatment.…”
Section: Discussionmentioning
confidence: 49%
“…There are some studies in which granular formulations of B. bassiana have been successfully applied for the control of soil pests, highlighting the preferability of this control method compared with the application of more common products, such as wettable powders or suspension concentrates (Kim et al, 2014b). Moreover, the Puyehue pyroclastic rock has been to replace perlite in the elaboration of substrates for greenhouse vegetable production because it is safe for plant growth (Schalamuk et al, 2014b), an important aspect that should be tested before its use in a formulation (Leggett et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of entomopathogenic fungi into potting soil using a solid-substrate culturing method or drenching the soil with a fungal suspension has shown significant efficacy against thrips (Ansari et al, 2007;Skinner et al, 2012). Millet-based granular formulations of entomopathogenic fungi, when applied to soil decreased rice water weevil, Lissorhoptrus oryzophilus populations up to 2 weeks after application (Kim et al, 2014). Lee et al (2017) reported 90% population reduction of WFT treated with granular formulations of B. bassiana 40 days after application.…”
Section: Introductionmentioning
confidence: 99%